Financial Management Behavior in Relation to Financial Literacy and Consumptive Behavior among Muslims in Walesi Village - Akbar, Taufiq (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
Consumptive behavior is a reflection of a person’s attitude in taking economic actions based on desires or needs for a product. Consumptive behavior can also generally be influenced by financial literacy and the concept of financial management in a person, especially in the Muslim community. Therefore, this study seeks to reveal the role of financial management concepts in strengthening the relationship between financial literacy and consumptive behavior. This study uses a quantitative approach with a causal research design and explanatory research. The population in this study is the Muslim community in Walesi Village, Jayawijaya Regency, using a purposive sampling technique with 122 respondents. The data were analyzed using path analysis with the AMOS program. The findings indicate that financial literacy has a significant effect on consumptive behavior and significantly improves financial management. Financial management also shows a strong and significant effect on consumptive behavior. Furthermore, financial literacy indirectly influences consumptive behavior through financial management, confirming the mediating role of financial management. These results imply that enhancing financial literacy programs accompanied by stronger financial management practices can help communities reduce excessive consumption and encourage more responsible financial decision-making oriented toward long-term needs.